Effective application of midwifery early warning in predicting adverse obstetric outcomes and reducing obstetric morbidity in hospitals: A systematic literature review - Tri Agus Setyowati; Mekar Dwi Anggraeni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Several iterations of Early Warning Systems used in the birthing domain for the purpose of identifying and addressing early clinical hazards aim to prevent morbidity and mortality. The potential of early warning systems lies in their ability to improve the quality of health care and reduce the likelihood of maternal death. Purpose: To validate the effectiveness, accuracy and sensitivity of implementing different obstetric early warning systems and physiological triggers to predict morbidity in postnatal wards in high-risk women. Method: A systematic review was conducted in accordance with PRISMA guidelines to identify peer-reviewed studies on obstetric Early Warning Systems published between 2016 and 2023. The search spanned multiple databases, including Scopus, ScienceDirect, Research Rabbit, Google Scholar, and PubMed, and was supplemented by a review of relevant reference lists and professional organization websites. The review focused on studies evaluating the effectiveness, accuracy, and sensitivity of MEOWS, MEWC, OEWS, SMO, and SMS in predicting clinical deterioration and improving outcomes in hospitalized maternity patients. Studies involving pediatric or non-obstetric populations and qualitative designs were excluded. Due to heterogeneous findings, a narrative synthesis was applied. Results: Out of 1,152 identified articles, 20 met the inclusion criteria. These studies examined the predictive accuracy and sensitivity of midwifery Early Warning Systems (EWS) in relation to maternal morbidity and mortality. Eight studies focused on the systems’ effectiveness in improving clinical outcomes, while one addressed both aspects. Eight versions of the midwifery EWS were analyzed, most of which incorporated six core clinical parameters: pulse, respiratory rate, temperature, blood pressure, and level of consciousness. Eleven studies specifically evaluated the accuracy of these systems in enhancing clinical outcomes. Additionally, researchers contributed to the development of midwifery-specific EWS tools. Conclusion: The maternal early warning system has shown effectiveness in predicting severe morbidity among obstetric patients and mortality in critically ill cases. These systems hold promise for enhancing service quality, preventing the progression of maternal complications, and improving overall health outcomes. However, current evidence on their impact in reducing maternal mortality across all populations remains limited. Additionally, most versions rely on clinical parameters routinely collected from constrained resources, which may contribute to less-than-optimal outcomes. Suggestion: A validated and standardized national obstetric early warning tool will enable the consistency and uniform approach needed in the assessment and management of potentially deteriorating conditions of pregnant women and compliance of health workers in implementing obstetric early warning tools according to standards.